(تەمەن) لە دیدی مەولانای ڕۆمی و مەولەوی تاوگۆزییەوە - حەمەکەریم, سەبور عەبدولکەریم (Sulaimani Journal for Humanities, 2022)
This study (Age from the viewpoint of both Mawlanay Rumi and Mawlawi Tawgozi) is an intertextual study between the poems of the Kurdish poet (Mawlawi) and the Persian Poet (Mawlanai Rumi). The paper tries to investigate and research the poets’ ideas of Age. As far as we are aware, this is the first study of its kind inside and outside Kurdistan that looks into the ideas and understandings of both poets on age in terms of concept and method of expression from both poets. The paper consists of an introduction, two parts, conclusions and the summary of the study in Arabic and English languages. In the first part, both poets’ ideas and understandings of the concept of age is introduced in an intertextual manner. In the second part, we have found out that five ideas about age do exist with Mawlana whilst they are absent in Mawlawi’s poems. The paper is concluded with the important findings and the list of references.